Association between maternal serum 25-hydroxyvitamin D level and pre-eclampsia. (17th June 2016) - Arisoy, Resul; Bostancı, Evrim; Erdogdu, Emre; Polat, Mesut; Kaya, Erdal; Tugrul, Semih
Abstract: Objectives : The objective of the study was to evaluate the association of maternal plasma levels of 25-hydroxyvitamin D (25(OH)D) at late second and third trimester and the risk of pre-eclampsia. Methods : In this prospective cohort study, maternal plasma 25(OH)D levels were measured at late second and third trimester in 77 women who later developed pre-eclampsia (31 non-severe and 46 severe cases) and 180 women without pre-eclampsia. Results : The mean gestational age of the timing of the blood sampling was 31.1 ± 4.4 at control group, 32.6 ± 5.7 at non-severe pre-eclamptic group and 32.3 ± 5.4 at severe pre-eclamptic group. The mean 25(OH)D concentration was significantly low in severe pre-eclampsia group (5.8 ± 4.5 ng/ml) than non-severe pre-eclampsia (11.8 ± 7.3 ng/ml, p  = 0.039) and control groups (14.9 ± 12.0 ng/ml, p  < 0.0001). There was no statistically significant difference in 25(OH)D concentration between non-severe pre-eclamptic and control groups ( p  = 0.404). In women with 25(OH)D concentration <20 ng/ml, a 12.45-fold increase in the odds of severe pre-eclampsia were detected. Conclusion : Women with severe pre-eclampsia had low serum 25(OH)D levels. The correlation between maternal 25(OH)D levels and aspartate aminotransferase, alanine transaminase, serum creatinine levels, platelet count were not determined. 25(OH)D levels may be used as an independent predictive marker of severe pre-eclampsia.